2021
DOI: 10.3233/jhd-210485
|View full text |Cite
|
Sign up to set email alerts
|

Association Analysis of Chromosome X to Identify Genetic Modifiers of Huntington’s Disease

Abstract: Background: Huntington’s disease (HD) is caused by an expanded (>35) CAG trinucleotide repeat in huntingtin (HTT). Age-at-onset of motor symptoms is inversely correlated with the size of the inherited CAG repeat, which expands further in brain regions due to somatic repeat instability. Our recent genetic investigation focusing on autosomal SNPs revealed that age-at-onset is also influenced by genetic variation at many loci, the majority of which encode genes involved in DNA maintenance/repair processes and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Recently, variants within the MSH3 / DHFR locus—a proven source of the dynamic mutation instability in finally differentiated brain tissue 19 —have been found to be stronger modifiers of the diagnostic motor signs in women when analyses were set as sex-specific 11 . Moreover, X-chromosome-wide association study (XWAS) found a variant close to the moesin gene potentially modifying AO 36 . Differences in AO of HD between genders have previously been reported for carriers of different genotypes within the APOE gene 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, variants within the MSH3 / DHFR locus—a proven source of the dynamic mutation instability in finally differentiated brain tissue 19 —have been found to be stronger modifiers of the diagnostic motor signs in women when analyses were set as sex-specific 11 . Moreover, X-chromosome-wide association study (XWAS) found a variant close to the moesin gene potentially modifying AO 36 . Differences in AO of HD between genders have previously been reported for carriers of different genotypes within the APOE gene 24 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, since RPA4 but not RPA1, RPA2, or RPA3, preferentially associates with MSH3 (Figure 4C), one can imagine Alt-RPA working with MutSβ, (MSH2-MSH3) to mediate CAG repeat expansions, possibly through retention of the excess repeats in poorly repaired slip-outs (Figure 2). Our data now reveal RPA1-4 as key players in CAG instability, despite the fact that RPA1-4, like MSH2, were not identified in the disease modifier screens [11][12][13][14][15]128 . Beyond repeat diseases, these RPA subunit BioID data provide a myriad of potential Alt-RPA↔RPA interactions which can shed light on a many metabolic pathways.…”
Section: Discussionmentioning
confidence: 99%